Two‐year outcomes in de novo renal transplant recipients receiving everolimus‐facilitated calcineurin inhibitor reduction regimen from the TRANSFORM study. Issue 11 (1st July 2019) - Berger, Stefan P.; Sommerer, Claudia; Witzke, Oliver; Tedesco, Helio; Chadban, Steve; Mulgaonkar, Shamkant; Qazi, Yasir; de Fijter, Johan W.; Oppenheimer, Federico; Cruzado, Josep M.; Watarai, Yoshihiko; Massari, Pablo; et al.
Abstract : TRANSFORM (TRANSplant eFficacy and safety Outcomes with an eveRolimus‐based regiMen) was a 24‐month, prospective, open‐label trial in 2037 de novo renal transplant recipients randomized (1:1) within 24 hours of transplantation to receive everolimus (EVR) with reduced‐exposure calcineurin inhibitor (EVR + rCNI) or mycophenolate with standard‐exposure CNI. Consistent with previously reported 12‐month findings, noninferiority of the EVR + rCNI regimen for the primary endpoint of treated biopsy‐proven acute rejection (tBPAR) or estimated glomerular filtration rate (eGFR) <50 mL/min per 1.73 m 2 was achieved at month 24 (47.9% vs 43.7%; difference = 4.2%; 95% confidence interval = −0.3, 8.7; P = .006). Mean eGFR was stable up to month 24 (52.6 vs 54.9 mL/min per 1.73 m 2 ) in both arms. The incidence of de novo donor‐specific antibodies (dnDSA) was lower in the EVR + rCNI arm (12.3% vs 17.6%) among on‐treatment patients. Although discontinuation rates due to adverse events were higher with EVR + rCNI (27.2% vs 15.0%), rates of cytomegalovirus (2.8% vs 13.5%) and BK virus (5.8% vs 10.3%) infections were lower. Cytomegalovirus infection rates were significantly lower with EVR + rCNI even in the D+/R− high‐risk group ( P < .0001). In conclusion, the EVR + rCNI regimen offers comparable efficacy and graft function with low tBPAR and dnDSA rates and significantly lower incidence of viral infections relative to standard‐of‐care up to 24 months. Clinicaltrials.gov number: NCT01950819. Abstract : Two‐year follow‐up findings from TRANSFORM, the largest study in de novo renal transplantation to date, demonstrate that everolimus‐facilitated calcineurin inhibitor reduction provides a valid alternative to standard‐of‐care immunosuppression comprising mycophenolate with standard calcineurin inhibitor by offering comparable antirejection efficacy, stable renal function, and significant benefit in protecting from viral infections.